Biomimetic carbon monoxide delivery based on hemoglobin vesicles ameliorates acute pancreatitis in mice via the regulation of macrophage and neutrophil activity - Kazuaki Taguchi; Saori Nagao; Hitoshi Maeda; Hiroki Yanagisawa; Hiromi Sakai; Keishi Yamasaki; Tomohiko Wakayama; Hiroshi Watanabe; Masaki Otagiri; Toru Maruyama (Taylor & Francis Group, 2018)
Macrophages play a central role in various inflammatory disorders and are broadly divided into two subpopulations, M1 and M2 macrophage. In the healing process in acute inflammatory disorders, shifting the production of M1 macrophages to M2 macrophages is desirable, because M1 macrophages secrete pro-inflammatory cytokines, whilst the M2 variety secrete anti-inflammatory cytokines. Previous findings indicate that when macrophages are treated with carbon monoxide (CO), the secretion of anti-inflammatory cytokine is increased and the expression of pro-inflammatory cytokines is inhibited, indicating that CO may have a potential to modulate the production of macrophages toward the M2-like phenotype. In this study, we examined the issue of whether CO targeting macrophages using a nanotechnology-based CO donor, namely CO-bound hemoglobin vesicles (CO-HbV), modulates their polarization and show therapeutic effects against inflammatory disorders. The results showed that the CO-HbV treatment polarized a macrophage cell line toward an M2-like phenotype. Furthermore, in an in vivo study using acute pancreatitis model mice as a model of an inflammatory disease, a CO-HbV treatment also tended to polarize macrophages toward an M2-like phenotype and inhibited neutrophil infiltration in the pancreas, resulting in a significant inflammation. In addition to the suppression of acute pancreatitis, CO-HbV diminished a subsequent pancreatitis-associated acute lung injury. This could be due to the inhibition of the systemic inflammation, neutrophil infiltration in the lungs and the production of HMGB-1. These findings suggest that CO-HbV exerts superior anti-inflammatory effects against inflammatory disorders via the regulation of macrophage and neutrophil activity.